Coagulation indices in very preterm infants from cord blood and postnatal samples. (25th September 2015) - Neary, E.; McCallion, N.; Kevane, B.; Cotter, M.; Egan, K.; Regan, I.; Kirkham, C.; Mooney, C.; Coulter‐Smith, S.; Ní Áinle, F.
Summary: Background: Very premature infants are at high risk of bleeding complications; however, few data exist on ranges for standard coagulation tests. Objectives: The primary objective of this study was to measure standard plasma coagulation tests and thrombin generation in very premature infants compared with term infants. The secondary objective was to evaluate whether an association existed between coagulation indices and intraventricular hemorrhage (IVH). Patients/Methods: Cord and peripheral blood of neonates < 30 weeks gestational age (GA) was drawn at birth, on days 1 and 3 and fortnightly until 30 weeks corrected gestational age. Prothrombin time (PT), activated partial thromboplastin time (APTT), fibrinogen and coagulation factor levels were measured and tissue factor‐stimulated thrombin generation was characterized. Control plasma was obtained from cord blood of term neonates. Results: One hundred and sixteen infants were recruited. Median (range) GA was 27.7 (23.7–29.9) weeks and mean (SD) birth weight was 1020 (255) g. Median (5th–95th percentile) day 1 PT, APTT and fibrinogen were 17.5 (12.7–26.6) s, 78.7 (48.7–134.3) s and 1.4 (0.72–3.8) g L −1, respectively. No difference in endogenous thrombin potential between preterm and term plasma was observed, where samples were available. Levels of coagulation factors II, VII, IX and X, protein C, protein S and antithrombin were reduced in preterm compared with term plasma. Day 1 APTT and PT were not associated with IVH. Conclusion: In the largest cross‐sectional study to date of very preterm infants, typical ranges for standard coagulation tests were determined. Despite long clotting times, thrombin generation was observed to be similar in very preterm and term infants.